KOMUNIKASI PARIWISATA EDUKATIF DALAM PENGUATAN KESADARAN BUDAYA LOKAL PADA ANAK USIA DINI DI PRATAMA WIDYALAYA DHARMA KUMARA - Harining, Ni Luh Senja; Suardana, I Ketut Putu (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
This study aims to examine educational tourism communication in strengthening local cultural awareness among early childhood students at Pratama Widyalaya Dharma Kumara, Mataram City. The research employed a descriptive qualitative method through observation, interviews, and documentation. The findings reveal that educational tourism communication is implemented through the introduction of folklore, traditional games, and visits to local cultural destinations. Children actively engage in experience-based activities that reinforce their sense of identity, pride, and concern for local culture. The study formulates a direct interaction-based communication model that involves teachers, educational media, and experiential learning approaches. This model effectively builds cultural awareness from an early age while supporting the promotion of educational tourism. The findings are expected to serve as a reference for the development of educational tourism programs in other early childhood institutions